Enhancement of the Power Conversion Efficiency in Organic Photovoltaics by Unveiling the Appropriate Polymer Backbone Enlargement Approach - Chochos, Christos L.; Singh, Ranbir; Kim, Min; Gasparini, Nicola; Katsouras, Athanasios; Kulshreshtha, Chandramouli; Gregoriou, Vasilis G.; Keivanidis, Panagiotis E.; Ameri, Tayebeh; Brabec, Christoph; Cho, Kilwon; Avgeropoulos, Apostolos (Advanced Functional Materials, 2016)
Optoelectronic properties, supramolecular assemblies, and morphology variation of polymeric semiconductors are governed by six fundamental chemical features. These features are molecular weight, bond length alternation (BLA), planarity, aromatic resonance energy, substituents, and intermolecular interactions. Of these features the specific role of BLA in determining the performance of a polymeric semiconductor in practical technological applications is so far unknown. This study investigates this question and reports the novel finding that the optoelectronic, microscopic (supramolecular packing), and macroscopic (morphology variation and device performance) properties of model semiconducting polymers depend on the conjugated polymer backbone enlargement, which is directly related to the BLA. Extensive studies are performed in both single-component polymer films and their blends with fullerene derivatives. Understanding the specific structure-properties relations will lead to significant advancement in the area of organic electronics, since it will set new design rules toward further optimization of polymer chemical structures to enhance the device performances. An efficient way to enlarge the polymer backbone of an electron donor conjugated polymer toward higher organic photovoltaic performance is presented.
Keywords: morphology; organic electronics; polymer semiconductors; recombination dynamics; supramolecular assembly